Detection of mecA and ermC genes in S. epidermidis isolates among acne patients - Muter, Baydaa shaheed; Zainab Dakhil Degaim, (University of Thi-Qar Journal of Science, 2023)
The purpose of the recent study was to profile of two resistance genes (mecA and ermC) in S.epidermidis which isolated from acne patients. In the study, 150 samples of acne from acne sufferers were collected between August and September 2022 in a private clinical place in the Thi-Qar province of Iraq. The S. epidermidis was only found in (40%) isolates.  Microscopical examination, morphological characterization , diverse biochemical testes, and accurate identification with Viteks-system were used to recognize S. epidermidis isolates.. The PCR technique  results recorded that (90%) of S. epidermidis isolates had mecA genes and low  percentage  of ermC (10%).